GE_GERICHTE C/21335/2008 vom 2. April 2009 - GE Cour de justice (2009)
; CHANGEMENT DE PRATIQUE ; MEILLEURE FORTUNE ; OPPOSITION(LP) ; LETTRE ; PTT ; COMMUNICATION ; PRINCIPE DE LA RÉCEPTION | LP.265.A